Delayed presentation of transfusion-related acute lung injury in the emergency department - Jaradat, Ömer; Şahin, Burak; Dolu, Zafer (Scientific Reports in Medicine, 2025)
Transfusion-related acute lung injury (TRALI) is a life-threatening complication occurring within 6–72 hours post-transfusion, marked by acute hypoxemia and bilateral pulmonary infiltrates. Delayed TRALI, presenting 6–72 hours after transfusion, is often underrecognized due to its temporal dissociation from the transfusion event. We report an 80-year-old woman with hypertension and atrial fibrillation who developed delayed TRALI 48 hours after receiving erythrocyte suspension for upper gastrointestinal bleeding. She exhibited dyspnoea, hypoxemia, and bilateral pulmonary oedema, without signs of volume overload or infection. Treatment included non-invasive ventilation and diuresis, resulting in rapid recovery. This case underscores the need to consider delayed TRALI in elderly patients with new respiratory symptoms post-transfusion. Early recognition and supportive care are vital, as delayed TRALI can lead to severe respiratory failure. Preventive measures, like using fresher blood units and male-donor plasma, may mitigate risk. Clinicians should maintain a high suspicion for TRALI in high-risk populations to enhance outcomes.
Keywords: Transfusion-related acute lung injury; transfusion-associated circulatory overload; Blood products; Transfusion